Sport in Aotearoa/New Zealand
1 online resource
Keywords: "This fascinating book investigates the sporting traditions, successes, systems, 'terrains', and contemporary issues that underpin sport in New Zealand, also known by its Māori name of Aotearoa. The book unpacks some of the 'cliches' around the place, prominence and impact of sport and recreation in Aotearoa/New Zealand in order to better understand the country's sporting history, cultures, institutions and systems, as well as the relationship between sport and different sections of society in the country. Exploring traditional sports such as rugby and cricket, indigenous Māori sport, outdoor recreation, and contemporary lifestyle and adventure sports such as marching and parkour, the book examines the contested and conflicting societal, geographical and managerial issues facing contemporary Aotearoa/New Zealand sport. Essential reading for anybody with a particular interest in sport in Aotearoa/New Zealand, this book is also illuminating reading for anybody working in the sociology of sport, sport development, sport management, sport history, or the wider history, politics and culture of Aotearoa/New Zealand or the South Pacific"--